Bibliometric analysis of research trends on rotary dryers using the VOSviewer application base on the Scopus database - Abdul Mukhlis Ritonga; Joko Nugroho Wahyu Kariadi; Rudiati Evi Masithoh; Redika Ardi Kusuma (Agrointek)
Bibliometric analysis is a crucial way to understand trends and progress in a field of research. Using the VOSviewer application for bibliometric analysis becomes an effective tool to demonstrate research patterns, networking, and research focus. This study explains the analysis of scientific publications related to rotary dryers using the VOSviewer application. This study aims to find trends through analyzing bibliometric data on rotary dryer research for 10 years (2014–2023). Data was collected from the Scopus database. The method used is descriptive causality, using VOSviewer to visualize relationships between keywords, authors, institutions, countries, and network collaborations between authors. The study showed 1,356 articles relevant to rotary dryers between 2014 and 2023. After elimination by document type (article, conference paper, review, and conference review) and language type (English), 465 articles were obtained. The bibliometric analysis results show changes in research trends, from performance studies to the study of the use of energy resources in rotary dryers and their integration with intelligent systems. There are five keyword clusters, with primary keywords in each cluster. The number of articles on the topic of rotary dryers has increased from year to year, with China being the country with the most publications and citations. Still, the number of links and strength of the author's relationship with other countries in carrying out joint publications remain relatively low. The results of this bibliometric analysis provide a helpful overview of research progress and prospects with the topic of rotary dryers and help the authors plan further research.